Immunomodulatory factors CRP/albumin ratio and NLR predict post-spinal surgery infection - Yuping, Chang; Rong, Wei; Fengjuan, Li; Chunhua, Liu; Zhenghui, Dong (Frontiers in Surgery, 2025)
ObjectiveThe objective of this work is to investigate the predictive value of the neutrophil-to-lymphocyte ratio (NLR) combined with the C-reactive protein/albumin (CRP/ALB) ratio for postoperative infections in patients undergoing spinal surgery.MethodsAccording to the inclusion criteria, 380 patients who underwent spinal surgery treatment in the Sixth Affiliated Hospital of Xinjiang Medical University between January 2020 and December 2023 were retrospectively screened and divided into two groups based on whether they were infected after surgery. The two groups were 1. infected group (n = 79) and 2. uninfected group (n = 301). The following variables were reviewed in both groups: gender, age, body mass index, hypertension, diabetes mellitus, coronary artery disease, history of smoking, history of alcohol consumption, duration of surgery, site of surgery, presence of blood transfusion, presence of internal fixation, NLR and CRP/ALB ratio. A one-way analysis was performed on these factors, and those with a P < 0.05 were replaced with a binary logistic analysis in order to investigate the factors associated with postoperative infection.ResultsComparative analysis revealed significant between-group differences (P < 0.05) in age, diabetes status, operative duration, blood transfusion, internal fixation use, postoperative NLR, and CRP/ALB ratio. Binary logistic regression identified six independent risk factors: advancing age (OR = 1.145, 95% CI 1.098–1.203), prolonged operative time (OR = 1.020, 95% CI 1.010–1.030), intraoperative blood transfusion (OR = 2.941, 95% CI 1.245–7.211), internal fixation placement (OR = 8.022, 95% CI 2.710–25.615), elevated postoperative NLR (OR = 1.870, 95% CI 1.531–2.324), and increased CRP/ALB ratio (OR = 2.178, 95% CI 1.673–2.943). All associations reached statistical significance (P < 0.001 unless specified).ConclusionThe results indicate that age, duration of surgery, blood transfusion, internal fixation, postoperative NLR and postoperative CRP/ALB are risk factors for the development of infection after spinal surgery. Surgeons should perform a thorough assessment of their patients in order to more accurately predict their likelihood of infection and to provide a basis for individualised treatment plans to reduce the risk of postoperative infections.